Improved skin wound healing activity of insulin cream as evidenced from the morphological evaluation in guinea pigs - Mohamed, Nur-Aliana Hidayah; Mokhtar, Rafidah Hanim; Al-Ani, Imad Matloub Dally; Ayob, Azizi; Misran, Misni (Universitas Indonesia, 2018)
Background: There is no histological study evaluating the effects of insulin-containing cream on skin injury. The goal of this study was to examine the effects of insulin-containing creams on wound healing. Methods: Creams consisting of nine parts of oil and one part of aqueous phase (9:1) mixed with 1.5 mL human insulin were prepared. Eighteen male guinea pigs were divided into three groups; the control (9:1 C) group received cream without insulin. The experimental groups received Humulin N (9:1 N) and Humulin R (9:1 R) respectively. A 1 cm2 wound of 1-2 cm thickness was created in the skin. Each animal received 0.5 g of the respective creams which was topically applied once a day for 14 days. The progress of wound healing was monitored daily. Skin tissues were excised at the 14th days from the wound sites and processed for light microscopy. Results: Skin wound treated with the long acting insulin Humulin N had an accelerated wound healing process with restoration of vascular network, increased collagen deposition and early complete wound remodeling. Conclusion: Insulin cream with long acting mechanism facilitates in normalizing cell permeability, promoting vascularization, reducing exudation and stimulate proliferation of cells. These properties render insulin cream suitable for expediting wound healing.